Electropolymerization and properties of poly (3-anilinethiophene) thin film - Saengrawee Sriwichai (2018)
© 2016, Chiang Mai University. All rights reserved. The poly(3-anilinethiophene) (P3AT) thin film was prepared by electropolymerization of its monomer, 3-anilinethiophene, on indium tin oxide (ITO) and gold-coated high refractive index glass substrates which were also used as working electrodes in electrochemical measurements. The obtained film was characterized by UV-vis absorption, Fourier-transform infrared (FT-IR) and surface plasmon resonance (SPR) spectroscopy which indicating the formation of P3AT on the substrates. The UV-vis and FT-IR results confirmed the formation of this polythiophene homopolymer containing primary amine groups as substituent groups. The surface morphology of the films after applying various constant potentials (-0.2, 0.5 and 0.6 V) compared with open circuit potential in neutral phosphate buffered saline (pH 7.4) solution was studied by atomic force microscopy (AFM). The P3AT film at different applied potentials showed different surface morphologies and roughnesses. The obtained polymer film should be suitable for construction of immunosensors in the future.